Eco-Sensing System for Water Pollution and Microplastic Detection - Vaishali Singh,; Soumya Verma,; Ayush Srivastava,; Abhishek Dubey,; Dr. Nikhat Akhtar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Microplastic contamination in aquatic habitats is a critical environmental concern, endangering marine organisms and human health. Conventional detection and remediation techniques often prove insufficient, prompting the need for the creation of novel strategies. This study seeks to investigate and assess innovative methods for identifying and reducing microplastics in aquatic ecosystems. The research examines sophisticated detection technologies, such as spectroscopy and sensor-based techniques, which provide enhanced accuracy and efficiency relative to traditional methods. Furthermore, it examines novel remediation methods, including bioremediation and the use of sophisticated filtering systems. The growing prevalence of microplastics and chemical pollutants in aquatic environments is a significant threat to ecosystems and human health. Traditional detection technologies are often laboratory-based, costly, and inappropriate for real-time or field applications. The system utilizes a mix of physical filtration, image processing, and miniaturized spectroscopy for microplastic detection, in conjunction with a suite of chemical sensors for real-time water quality assessment. The findings reveal that these novel techniques significantly improve the identification and elimination of microplastics, exhibiting enhanced efficacy compared to conventional methods. This study offers essential insights into the capacity of innovative technologies to mitigate microplastic pollution, emphasizing their relevance and advantages for environmental conservation. Integrating these creative technologies will enhance the protection of aquatic habitats and foster sustainable environmental practices.
Keywords: Microplastics; Water Systems; Environmental Factors; Ecosystems; Pollution Prevention; Distribution Characteristics